Quantitative PCR for detection of Citrus tristeza virus in Colombia (2018)
Real-time quantitative PCR (qRT-PCR) was applied using SYBR Green for the specific detection of Citrus tristeza virus (CTV) in Colombian. Genomic RNA (gRNA) was amplified using primers designed from conserved sequences in the open reading frames (ORF’s) 1b and 2. We obtained a 186 bp product with neither dimers nor non-specificity. The analysis of the melting curve showed a peak between 81 °C and 83 °C, with a correlation coefficient of 0.998 and an efficiency of 99.1 %. The amplification of the 186 bp fragment resulted in the standard curve, which allowed the quantitative analysis of the samples with a detection range between 1x108 and 1x103 genomic RNA copies, with low variation coefficients. CTV accumulation was higher in foliar and fruit tissue than in the bark, and the differences observed among several citrus species susceptible to infection were minimal. The highest concentration of virus was found in the upper third of the analyzed plants, followed by the lower third and finally the middle third. The qRT-PCR is a specific and sensitive method, with a practical interest for the detection of viral diseases in citrus plants and other crops of commercial interest.